2010
DOI: 10.1674/0003-0031-163.1.161
|View full text |Cite
|
Sign up to set email alerts
|

Allelopathic Effects of Goldenrod Species on Turnover in Successional Communities

Abstract: ABSTRACT.-While goldenrod species are often found to be allelopathic in laboratory settings, its importance in controlling plant community dynamics has been much more difficult to assess. We designed a study to determine whether allelopathy is related to the success of goldenrods in abandoned agricultural land. To accomplish this, we conducted laboratory bioassays for six co-occurring goldenrod species and compared these results to the cover and impacts of these species in the field. We determined the germinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
20
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 31 publications
4
20
1
1
Order By: Relevance
“…However, the range of allelopathic potential for the invasive species tested here is similar to that documented for some native species from the same site. For example, native goldenrod (Solidago) species are often linked with allelopathy (Abhilasha et al 2008, Pisula andMeiners 2010). Using the same method as this study, three out of six goldenrod species had beta values that were within the range found in this survey of non-natives (Pisula and Meiners 2010).…”
supporting
confidence: 61%
See 3 more Smart Citations
“…However, the range of allelopathic potential for the invasive species tested here is similar to that documented for some native species from the same site. For example, native goldenrod (Solidago) species are often linked with allelopathy (Abhilasha et al 2008, Pisula andMeiners 2010). Using the same method as this study, three out of six goldenrod species had beta values that were within the range found in this survey of non-natives (Pisula and Meiners 2010).…”
supporting
confidence: 61%
“…For example, native goldenrod (Solidago) species are often linked with allelopathy (Abhilasha et al 2008, Pisula andMeiners 2010). Using the same method as this study, three out of six goldenrod species had beta values that were within the range found in this survey of non-natives (Pisula and Meiners 2010). The remaining goldenrod species were more toxic than any of the invasive species tested (b values ranging from 20.59 to 20.74, Pisula and Meiners 2010).…”
supporting
confidence: 54%
See 2 more Smart Citations
“…The negative effect of goldenrods on the number of species may be both direct and indirect. Goldenrods out-compete native plants and change the habitat structure, soil properties and microclimatic characteristics (VoserHuber 1992;Weber 2001;de Groot et al 2007;Pisula and Meiners 2010). Interestingly, the most abundant species in the grasslands with goldenrods were M. scabrinodis, M. rubra and Lasius niger.…”
Section: Discussionmentioning
confidence: 99%